Transcultural Adaptation and Psychometric Proprieties of the Mental Toughness Inventory for Brazilian Athletes - Moreira, Caio Rosas; Codonhato, Renan; Fiorese, Lenamar (Frontiers in Psychology, 2021)
This study has assessed the psychometric proprieties of the Mental Toughness Inventory (MTI) within the context of Brazilian sports. Twelve professionals participated in the process of adapting and translating the scale to Brazilian Portuguese. Subjects were 575 athletes (23.54±5.79 years old; 58% males) who answered the MTI and the 10-item Connor-Davidson Resilience Scale. Data was analyzed through Confirmatory Factor Analysis (CFA), Cronbach’s alpha, Composite Reliability, Average Variance Extracted, Spearman correlation and Model Invariance tests. Results from CFA showed adequate fit for the scale’s original 8-item structure (χ2=27.041; p=0.078; χ2/df=1.50; CFI=0.988; TLI=0.981; RMSEA=0.03 [0.00-0.05]; SRMR=0.030) assessing mental toughness as a single factor and the scale presented satisfactory internal consistency (CR=0.81; α=0.82). Mental toughness was correlated with resilience (r=0.607), age (r=0,276) and time of experience in the sport (r=0,215). The MTI has also shown partial measurement invariance for sex and complete invariance across sport types. It was concluded that the MTI is a suitable tool for assessing mental toughness in the present sample of Brazilian athletes; this instrument has potential practical application for researchers and sport psychologists who seek to develop athletes’ well-being and performance